Numerical Study on 4-1 Coal Seam of Xiaoming Mine in Ascending Mining. (17th March 2015) - Tianwei, Lan; Hongwei, Zhang; Sheng, Li; Jun, Han; Weihua, Song; Batugin, A. C.; Guoshui, Tang
Abstract : Coal seams ascending mining technology is very significant, since it influences the safety production and the liberation of dull coal, speeds up the construction of energy, improves the stability of stope, and reduces or avoids deep hard rock mining induced mine disaster. Combined with the Xiaoming ascending mining mine 4-1, by numerical calculation, the paper analyses ascending mining 4-1 factors, determines the feasibility of ascending mining 4-1 coalbed, and proposes roadway layout program about working face, which has broad economic and social benefits.